Generating long‐wavelength absorption bands with enhanced deep red fluorescence and photothermal performance in fused carbon dots aggregates. Issue 6 (28th October 2021) - Wu, Jun; Lei, Josh Haipeng; He, Bingchen; Deng, Chu‐Xia; Tang, Zikang; Qu, Songnan
Abstract: Carbon dots (CDs) with long‐wavelength absorptions and emissions are highly desired for biological applications. Herein, we report a new supra‐CDs strategy to construct long‐wavelength absorption bands based on fused CDs aggregates (f‐CDAs) through a concentration‐induced interparticle dehydration process among green emissive CDs (r‐CDs) under solvothermal treatment. The obtained fused f‐CDAs exhibit an obvious absorption band in 550–700 nm and significantly enhanced deep red fluorescence in N, N ‐dimethylformamide with photoluminescence quantum yields of 15.6% and high photothermal conversion efficiency up to 26.1% in water. Benefiting from the high photothermal performance, in vivo tumor photothermal therapy has been realized via intratumoral injection of f‐CDAs under 655 nm laser irradiated at 0.5 W/cm 2 . Abstract : A new supra‐carbon dots (CDs) strategy based on fused CDs aggregates (f‐CDAs) is demonstrated via concentration‐induced dehydration among CDs. Deriving from the fusing interfaces, long absorption bands with enhanced deep red emission are constructed in f‐CDAs, which can lead to the high photothermal performance in water for tumor photothermal therapy.